Challenges in Diagnosing Leprosy Mimicking Tinea Versicolor - Surender Benedict; Zulkifli Harun; Masri Quak Saifuddin (Sumatera Medical Journal, 2026)
Background: Leprosy is a significant concern within the medical fraternity due to its enduring prevalence across various countries. It is frequently misdiagnosed due to its clinical presentation, which can closely resemble that of tinea versicolor. Objective: This case report highlights a 26-year-old Orang Asli woman from Pekan, Pahang, who exhibited multiple hypopigmented lesions on her right flank for 1 year. Initially misdiagnosed as tinea versicolor by a general practitioner, her condition showed no improvement despite appropriate antifungal treatment. The patient’s history revealed close contact with persons with leprosy, and she resides in an endemic area. Methods: A clinical assessment was conducted, including medical history, contact history, and physical examination. A slit-skin smear was performed to establish the diagnosis. Results: A skin slit smear was performed, which yielded positive results and confirmed multibacillary leprosy. Consequently, multidrug therapy was promptly initiated in the primary care clinic. The lesions improved, indicating a positive response to multidrug therapy (MDT). Conclusion: This case underscores the critical importance of maintaining a high index of suspicion for leprosy in endemic regions, particularly when patients present with lesions that may masquerade as other dermatological conditions.